Six-coordinate zinc porphyrins for template-directed synthesis of spiro-fused nanorings. - Favereau, L; Cnossen, A; Kelber, J; Gong, J; Oetterli, R; Cremers, J; Herz, L; Anderson, H (American Chemical Society, 2015)
Five-coordinate geometry is the standard binding mode of zinc porphyrins with pyridine ligands. Here we show that pseudo-octahedral six-coordinate zinc porphyrin complexes can also be formed in solution, by taking advantage of the chelate effect. UV-vis-NIR titrations indicate that the strength of this second coordination is ca. 6-8 kJ mol(-1). We have used the formation of six-coordinate zinc porphyrin complexes to achieve the template-directed synthesis of a 3D π-conjugated spiro-fused array of 11 porphyrin units, covalently connected in a nontrivial topology. Time-resolved fluorescence anisotropy experiments show that electronic excitation delocalizes between the two perpendicular nanorings of this spiro-system within the experimental time-resolution of 270 fs.